Derivations of gamma (semi)hyperrings - Ardekani, L. K.; Davvaz, B. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
Differential Γ -(semi)hyperrings are Γ -(semi)hyperrings equipped with derivation, which is a linear unary function satisfying the Leibniz product rule.We introduce the notions of derivation and weak derivation on Γ -hyperrings and Γ -semihyperrings and obtain some important results relating to them in a specific way.